O2-S5.05 Are MSM looking for lesions? Examining self and partners for syphilis. (10th July 2011) - Surie, D; Koumans, E; Furness, B; Perkins, R; Brewer, T; Turner, D; Hernandez-Kline, P; Gamerdinger, K; Workowski, K; Markowitz, L
Abstract : Background: Syphilis rates among men who have sex with men (MSM) in the US are rising. In 2009, 62% of reported primary and secondary syphilis cases in the U.S. were among MSM. Self- and partner-examination for primary syphilis (painless chancre) might increase early detection and treatment and reduce transmission. As the first step in a study to increase syphilis lesion awareness, we collected baseline data on rates of self- and partner-examination. Methods: Data were collected from five MSM STD or infectious disease clinics in the US before and after introduction of brochures with pictures and information about syphilis signs, transmission, and prevention. Surveys included questions about demographics, sexual behaviours, syphilis knowledge and self- and partner-examination. Data were analysed using SAS V.9.2. Results: From September 2009 to January 2011, 586 sexually active men completed a survey; 124 (21%) from Arizona, 128 (22%) from the District of Columbia, 202 (34%) from Florida and 132 (22%) from Georgia; 542 (92.5%) reported having sex with men only and 44 (7.5%) reported having sex with men and women. Most participants (334, 57%) were aged 18–39 years, 240 (41%) were 40–59 years and 12 (2%) were older than 60 years; 222 (38%) reported one partner, 180 (31%) 2–3 partners, 133 (23%) 4–10 partners, and 51 (9%) >10 partners in the last 3 months or since their last clinic visit. Most participants correctly identified oral (510, 87%), anal (529, 90%) and oral-anal sex (487, 83%) as ways to transmit syphilis. Few recognised frottage that is, rubbing against someone (112, 19%) and kissing (196, 34%) as other modes of transmission. Over 50% reported self-examination of mouth, penis and skin at least once a week, whereas less than half reported partner-examination of these areas (Abstract O2-S5.05 table 1 ). Less than 50% reported self- or partner-examination of anus at least once a week. Rates of self-examination did not vary by number of partners or age; whereas, examining partner's mouth, penis and skin was less frequent (p<0.05) among MSM with >3 partners. Conclusions: The majority of MSM reported examining themselves at least once a week, but did not examine their partners as frequently. MSM with >3 partners were less likely to examine their partners' bodies than those with fewer partners. Analysis of surveys from men after brochure introduction will determine whether education materials increase rates of self- and partner-examination.